Chapter Assessment of the ecological status of Sicilian coastal waters according to a macroalgae based index (CARLIT) - Sirchia, Benedetto (Proceedings e report, 2020)
In the frame of the European Water Framework Directive (WFD, 2000/60/EC), a macroalgae based index (CARLIT) was applied along the Sicilian coastal water bodies (WBs) in order to assess for the first time their ecological status and collect accurate information on the distribution and abundance of shallow-water communities, especially of those most sensitive. The ecological quality ratio values, sensu WFD, showed "high"/"good" levels in all WBs with lushy forests of Cystoseira amentacea except two with "moderate" level due to the presence of stress-tolerant species related to local factors.